Fourth-Generation Warfare and Issues of National Security: Is Indonesia Ready? - Sunarko, Bagus Sigit (Global Strategis, 2026)
This article aims to assess Indonesia’s readiness to face security threats related to Fourth-Generation Warfare (4GW). The idea of 4GW refers to conflicts that involve non-state actors, blend political and military goals, and blur the line between soldiers and civilians. These types of conflicts often appear in rebellions, terrorism, and separatist movements that exploit a country’s internal weaknesses. In Indonesia, 4GW threats can be seen in separatist movements, terrorist networks, and anti-Pancasila groups that have challenged national stability since the early years of independence. This study finds that Indonesia’s long experience in dealing with rebellions, together with its “total defense” system, known as the Universal People’s Security and Defense System (Sishankamrata), gives the country a strong foundation to respond to asymmetric threats. The security structure, which integrates the military, police, and civilian participation, also strengthens Indonesia’s ability to manage internal conflict. These findings show that Indonesia’s hybrid defense model remains relevant for responding to the nature of 4GW threats today.Keywords: Fourth-Generation Warfare, Indonesia’s National Security, Separatist Movement, Sishankamrata, Terrorism Artikel ini bertujuan untuk menilai kesiapan Indonesia dalam menghadapi ancaman keamanan Perang Generasi Keempat (4GW). Konsep 4GW mengacu pada berbagai konflik yang melibatkan aktor non-negara, menggabungkan tujuan politik dan militer, serta menampilkan ketidakjelasan batas antara tentara dan warga sipil. Konflik semacam ini sering muncul dalam bentuk pemberontakan, terorisme, dan gerakan separatis yang mengeksploitasi kelemahan internal suatu negara. Di Indonesia, ancaman 4GW dapat dilihat dalam gerakan separatis, jaringan teroris, dan kelompok anti-Pancasila yang telah mengganggu stabilitas nasional sejak awal kemerdekaan. Studi ini menemukan bahwa pengalaman panjang Indonesia dalam menghadapi pemberontakan, bersama dengan sistem "pertahanan semesta" yang dikenal sebagai Sistem Pertahanan dan Keamanan Rakyat Semesta (Sishankamrata), memberikan landasan yang kuat bagi negara untuk merespons ancaman-ancaman yang berasal dari kekuatan yang bersifat asimetris. Struktur keamanan yang mengintegrasikan partisipasi militer, kepolisian, dan masyarakat sipil juga memperkuat kemampuan Indonesia dalam mengelola konflik internal. Temuan ini menunjukkan bahwa model pertahanan hibrida Indonesia tetap relevan untuk merespons sifat ancaman yang berasal dari 4GW saat ini. Kata-kata Kunci: Perang Generasi Keempat, Keamanan Nasional Indonesia, Gerakan Separatis, Sishankamrata, Terorisme